2015
DOI: 10.1161/atvbaha.114.304887
|View full text |Cite
|
Sign up to set email alerts
|

Class IA Phosphatidylinositol 3-Kinase Isoform p110α Mediates Vascular Remodeling

Abstract: Objective— Neointima formation after vascular injury remains a significant problem in clinical cardiology, and current preventive strategies are suboptimal. Phosphatidylinositol 3′-kinase is a central downstream mediator of growth factor signaling, but the role of phosphatidylinositol 3′-kinase isoforms in vascular remodeling remains elusive. We sought to systematically characterize the precise role of catalytic class IA phosphatidylinositol 3′-kinase isoforms (p110α, p110β, p110δ), which signal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 44 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…By using a gene silencing strategy, they confirmed an essential role for p110a in SMC proliferation following PDGF stimulation but surprisingly also identified that p110d silencing affected SMC proliferation, suggesting a non-catalytic role of this isoform downstream of PDGFR activation (Vantler et al, 2015). To further investigate a possible role for p110a in the restenosis process, the authors developed a mouse model where p110a had been specifically invalidated in SMC using the Cre/LoxP system with Cre expressed under the promoter of SM22a.…”
Section: Pi3k In Smooth Muscle Cellsmentioning
confidence: 96%
See 4 more Smart Citations
“…By using a gene silencing strategy, they confirmed an essential role for p110a in SMC proliferation following PDGF stimulation but surprisingly also identified that p110d silencing affected SMC proliferation, suggesting a non-catalytic role of this isoform downstream of PDGFR activation (Vantler et al, 2015). To further investigate a possible role for p110a in the restenosis process, the authors developed a mouse model where p110a had been specifically invalidated in SMC using the Cre/LoxP system with Cre expressed under the promoter of SM22a.…”
Section: Pi3k In Smooth Muscle Cellsmentioning
confidence: 96%
“…Different studies have recently investigated the possibility of blocking the activity of several class IA isoforms to prevent SMC proliferation in vitro and in vivo. In rat and human aortic SMC, Vantler et al found that the three class IA isoforms, a, b and d, were expressed whereas p110d was previously reported to be restricted to hematopoietic cells (Vantler et al, 2015).…”
Section: Pi3k In Smooth Muscle Cellsmentioning
confidence: 98%
See 3 more Smart Citations